Engaging Gen Z to Work Onsite: Role of Camaraderie and Readiness - Saragih, Eva Hotnaidah (Jurnal Aplikasi Manajemen, 2025)
In mid-2023, the pandemic in Indonesia was declared endemic. People returned to normal activities, including the workplace, which resumed on-site activities. Meanwhile, the workforce began to be dominated by Gen Z, who were accustomed to online activities, especially during the pandemic. Regarding this phenomenon, qualitatively, it was found that camaraderie was the most frequently and consistently cited factor by Gen Z that influences their readiness to work on-site. In this study, we want to see further: Does Camaraderie also influence Gen Z's engagement with work and the organization when they have to work onsite, and does Gen Z Readiness mediate this relationship? Because organizations need to be able to engage and retain Gen Z, not just make them ready when they have to return to work onsite. From the results of a survey of 298 respondents who met the criteria: active workers/employees, from Generation Z (born between 1997 and 2005), and currently working onsite, and the result of data processing using SMART-PLS4, it was found that Camaraderie had a significant positive effect on both Gen Z's Readiness and Engagement when having to return to work onsite. The results of the study, which found no significant effect of readiness on engagement, nor readiness as a mediator between camaraderie and engagement, suggest that readiness may not be a strong factor in shaping Gen Z's engagement in working onsite. This study demonstrates how organizations can engage Gen Z employees to work onsite by creating and strengthening camaraderie in the workplace, thereby enriching the academic literature and providing practical guidance for organizations and managers.